Systemic Mastocytosis with Smoldering Multiple Myeloma: Report of a Case - Sassine Ghanem; Gwenalyn Garcia; Liu Ying; Matthew Hurford; Marcel Odaimi (Case Reports in Oncological Medicine)
Systemic mastocytosis (SM) is a disease characterized by a clonal infiltration of mast cells affecting various tissues of the body. It is grouped into six different subtypes according to the World Health Organization classification. It is called indolent systemic mastocytosis (ISM) when there is no evidence of end organ dysfunction, while the presence of end organ dysfunction defines aggressive systemic mastocytosis (ASM). When SM coexists with a clonal hematological disorder, it is classified as systemic mastocytosis with associated clonal hematological nonmast cell lineage disease (SM-AHNMD). Over 80% of SM-AHNMD cases involve disorders of the myeloid cell lines. To our knowledge, there are only 8 reported cases to date of SM associated with a plasma cell disorder. We report a patient with ISM who was found to have concomitant smoldering multiple myeloma. His disease later progressed to ASM. We discuss this rare association between SM and a plasma cell disorder, and potential common pathophysiologic mechanisms linking the two disorders will be reviewed. We also discuss prognostic factors in SM as well as the management options considered during the evolution of the patient’s disease.